Leadership, Inside and Out - Gallagher, Deirdre; Shaffner, Joseph (Maine Policy Review, 2018)
This article explores leadership, inside and out: a new approach to equip aspiring leaders with the tools to lead creatively, inclusively, and effectively. Leadership, inside and out, transforms emerging leaders into the leaders of the future, positioning them to indelibly impact their own organizations and the state of Maine.